Short-range correlations in binary alloys: Spin model approach to AgcAu1-c and AgcPd1-c - Vilja I; Kokko K (ELSEVIER SCIENCE SA, 2022)
Short-range correlations in Ag-Au and Ag-Pd alloys are investigated by analyzing the ab initio total energy of face centered cubic (fcc) based random AgcAu1-c, and AgcPd1-c. Since the information on the atomic interactions is incorporated in the energetics of alloys it is possible with a suitable model, Bethe-Peierls-Weiss model is used in the present work, to invert the problem, i.e. to obtain information on the short-range correlation from the total energy of a random system. As an example we demonstrate how site correlations can be extracted from random alloy data. Bethe-Peierls-Weiss model predicts negative (positive) first neighbor correlator for substitutional fcc Ag-Au and (Ag-Pd) alloys at low temperature which can be related to the optimal structures of Ag0.5Au0.5 (and Ag0.5Pd0.5). (C) 2014 Elsevier B.V. All rights reserved.